Characterization of Thienylchalcones as hMAO‐B Inhibitors: Synthesis, Biochemistry and Molecular Dynamics Studies. Issue 34 (4th December 2017) - Mathew, Bijo; Uçar, Gülberk; Rapheal, Clariya; Mathew, Githa E.; Joy, Monu; Machaba, Kgothatso E.; Soliman, Mahmoud E. S.
Abstract: The design of selective, reversible and non‐toxic hMAO−B inhibitors has received increasing attention due to their perceived utility in targeting of neurological disorders like Alzheimer's and Parkinson's diseases. For this purpose, herein, we report the inhibitory studies on monoamine oxidase of a series of ( 2E )‐1‐(2, 5‐dichlorothiophen‐3‐yl)‐3‐(4‐substitutedphenyl) prop‐2‐en‐1‐ones (S1 ‐S9 ). All the compounds were found to be competitive, selective, and reversible inhibitors of hMAO−B except (2 E )‐1‐(2, 4‐dichlorothiophen‐3‐yl)‐3‐(4‐nitrophenyl) prop‐2‐en‐1‐one (S6 ) which is found to be non‐selective MAO inhibitor. The potent hMAO−B inhibitor, (2 E )‐1‐(2, 4‐dichlorothiophen‐3‐yl)‐3‐[4‐(dimethylamino) phenyl] prop‐2‐en‐1‐one (S4 ), showed a Ki value of 0.041 μM better than the standard drug, selegiline (hMAO−B with Ki = 0.302 μM). Moreover, S4, was nontoxic in cultured hepatic cells at 5 and 25 μM, with 94.44 and 88.00% viable cells, respectively. Molecular docking and molecular dynamics simulation studies were carried out using Autodock‐vina and Amber 14 to understand the molecular level interaction and energy relation of MAO isoforms with selective MAO−B inhibitor, S4 . Abstract : A series of ( 2E )‐1‐(2, 5‐dichlorothiophen‐3‐yl)‐3‐(4‐substitutedphenyl) prop‐2‐en‐1‐ones were synthesized and investigated for their human monoamine oxidase inhibitory studies. Molecular docking and molecular dynamics simulation studies were carried out using Autodock‐vina and Amber 14.